Molecular triage on HPV-positive samples in a cervical screening setting - Larsson, Gabriella Lillsunde; Carlsson, Jessica; Helenius, Gisela; Bergengren, Lovisa (PloS one, 2025)
To improve human papilloma virus (HPV) screening, more effective triage methods for HPV-positive samples need development and validation. Cytology, the most common triage method today, is subjective and can only be applied to professionally collected samples. Methylation status has been shown to be informative, as genes are highly methylated in HPV-induced cervical dysplasia and cancer. This study aimed to assess whether triaging HPV-positive samples using molecular methods, such as methylation and genotyping for high-risk HPV types, could be as effective as cytology in cervical screening. A retrospective biobank study was conducted on HPV-positive samples collected in 2017-2018, analyzing FAM19A4/MiR-124-2 hypermethylation and HPV genotyping for types 16, 18, 31, 33, 45, 52, and/or 59, comparing these results to cytology triage for detecting histologically confirmed high-grade squamous intraepithelial lesions (HSIL) and cancer. Results from 1915 positive screening samples were analyzed, including 1052 follow-up biopsies with 402 HSIL or cancer cases. Genotyping showed slightly higher sensitivity than cytology but lower specificity, while methylation had higher specificity but much lower sensitivity. Cytology's positive predictive value (PPV) was 36%, with lower PPVs for the molecular methods. Combining molecular methods increased the PPV but significantly reduced sensitivity. Based on these findings with molecular methods reducing sensitivity, we do not recommend adopting the molecular triage methods evaluated in this study in the Swedish setting. The trade-off between sensitivity and specificity does not support a change from the current cytology-based triage approach.